Enhancing the shopping experience through QR codes: the perspective of the Romanian users - Irina Albăstroiu; Mihai Felea (Amfiteatru Economic Journal, 2015)
The progress registered in the field of information and communication technologies has induced significant changes in the purchasing behaviour of the consumers who nowadays want simultaneous use of online and offline channels within the same shopping experience. QR Code (Quick Response) is among the emerging technologies that retailers can implement for adapting to these changes. Through reviewing the literature, the article firstly clarifies the characteristics and applicability of the QR codes, especially in retail, and then presents the results of an exploratory research conducted among Romanian users regarding their attitude and interest in QR codes. The objective of the research was to identify the degree of usage, the willingness of the Romanian people to use codes in the buying process and also their perception about the functionality and usefulness of the codes. This is a pioneering work for the Romanian literature, because there aren't other studies that explore issues concerning the use of QR codes in the buying process. Results of the study indicated that respondents know the applicability of QR codes and have used codes for accessing information about products and for online purchases and they consider that QR codes contribute to the improving of the shopping experience.
Keywords: O33; L81; 330; QR (Quick Response) code; technology; mobile device; mobile tagging; shopping experience; buying process